Of Missionaries, Multiculturalism, and Mainstream Malaise: Reflections on the “Presbyterian Predicament" - Banker, Mark (The journal of Presbyterian history, 2003)
Although mainstream Protestant missionaries were among the first institutional groups in United States history to engage in sustained encounters with “foreign" cultures and populations, few observes have considered the historical significance of the cultural interaction that occurred in the mission fields. Until recently church people typically viewed missionaries in hagiographic terms while academics, particularly since the 1960s, more often considered them agents of imperialism. Collectively, mission officials, church members, and mission historians focused on the impat, whether positive or negative, of mission work on the target populations. In this essay, the author recounts his evolution as mission historian and the professional and personal circumstances that led him to contemplate how service in the mission fields affected the missionaries—and particularly their understanding of cultural diversity. He concludes by speculating on the potential significance of his findings for the Presbyterian Church (U.S.A.) and other mainstream denominations as they seek to fulfill their calling in the increasingly multicultural twenty-first century.